Control of Plant Viruses by CRISPR/Cas System-Mediated Adaptive Immunity - Cao, Yongsen; Zhou, Huanbin; Zhou, Xueping; Li, Fangfang (Frontiers in Microbiology, 2020)
Plant diseases caused by invading plant viruses pose serious threats to agricultural production in the world, and the antiviral engineering initiated by molecular biotechnology has been an effective strategy to prevent and control plant viruses. Recent advances in clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) system-mediated DNA or RNA editing/interference in plants make them very attractive tools applicable to the plant protection field. Here, we review the development of CRISPR/Cas systems and summarize their applications in controlling different plant viruses by targeting viral sequences or host susceptibility genes. We list some potential recessive resistance genes that can be utilized in antiviral breeding and emphasize the importance and promise of recessive resistance gene-based antiviral breeding to generate transgene-free plants without developmental defects. Finally, we discuss the challenges and opportunities for the application of CRISPR/Cas techniques in the prevention and control of plant viruses in the field.